Enhancement of l-phenylalanine production by aminoacylase-chitosan complex / Pat M. Lee and Kong-Hung Lee - Lee, Pat M.; Lee, Kong-Hung (Faculty of Applied Sciences, 2004)
Aminoacylase (E.C.3.5.1.14) catalyses the enantioselective hydrolysis of N-acetyl-L-amino acids. It is immobilized by forming an insoluble complex with chitosan to produce Lphenylalanine from a racemic mixture of N-acetyl-DL-phenylalanine. The aminoacylasechitosan complex enhanced the yield of production of L-phenylalanine by about 400% at neutral pH, at 65 °c and at alkaline pH (7.5-8.5) at 37°c .